The Effect of Competency, Work Discipline, Team Work and Organization Support to Quality of Work Life, Satisfaction and Performance of Drivers Oto Bus Inter City in East Java - Lubis, Zulkifli; Purnomo, Wahyu; Felix Hutapea, Juan Felix Hutapea (one million dreams corporation, 2025)
This study is about the influence of competence, team work, organizational support, and work discipline, to the quality of work life, satisfaction, and performance of inter-city bus drivers in East Java Province. The study population is 367 inter-city bus drivers whose headquarters are in Gerbang-kertosusila East Java. Test model with Generalized Least Square Estimation (GLS), structural equation model (SEM) analysis, proportional random sampling method and Amos 22 software aid, on 250 respondents. The test results show the model (fit) seen from the value of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF, each of 0.928, 0.912, 0.958, 0.967, 0.082 and 1.734 are all within the expected range of values so that the model can be accepted. The results showed that: 1). Competence affect the quality of work life. 2). Competence affects driver satisfaction. 3). Competence affects the driver's performance. 4). Work discipline affect the quality of work life of the driver. 5). Work discipline affects driver satisfaction. 6). Work discipline affects the driver's performance. 7). Team work affects the quality of work life of the driver. 8). Team work has a significant influence on driver satisfaction. 9). Team work has an effect on the driver's performance. 10). Organizational support has an effect on the quality of work life. 11). Organizational support affects driver satisfaction. 12). Organizational support affects the driver's performance. 13) Quality of work life affect the driver's performance. 14) Job satisfaction has no significant effect on driver's performance